Health econometrics - Baltagi, Badi H. (Badi Hani); Moscone, Francesco (Contributions to economic analysis ;, 2018)
Recent years have witnessed a dramatic surge in applied econometric work in health economics, enhanced by the availability of large micro and macro data sets as well as the rapid development of new techniques and tools in econometrics. Health economics is an important and challenging area of research for applied econometricians, due to complexity embedded in the data, arising from issues such as nonlinearity of models, the presence of individual-level unobserved heterogeneity as well as time and cross sectional dependencies.This book covers a wide range of existing and emerging topics in applied health economics. These include: behavioural economics, medical care risk, social insurance, discrete choice models, cost-effectiveness analysis, health and immigration, vignette approach, response of parental investments to childs health at birth, determinants of innovation in the pharmaceutical industry, hospital competition, use of administrative data, spatial health econometrics, health expenditure, and networks.